Allopolyploidy, diversification, and the Miocene grassland expansion - Estep, Matt C.; McKain, Michael R.; Diaz, Dilys Vela; Zhong, Jinshun; Hodge, John G.; Hodkinson, Trevor R.; Layton, Daniel J.; Malcomber, Simon T.; Pasquet, Rémy; Kellogg, Elizabeth A. (Proceedings of the National Academy of Sciences - PNAS, 2014)
The role of polyploidy, particularly allopolyploidy, in plant diversification is a subject of debate. Whole-genome duplications precede the origins of many major clades (e.g., angiosperms, Brassicaceae, Poaceae), suggesting that polyploidy drives diversification. However, theoretical arguments and empirical studies suggest that polyploid lineages may actually have lower speciation rates and higher extinction rates than diploid lineages. We focus here on the grass tribe Andropogoneae, an economically and ecologically important group of C ₄ species with a high frequency of polyploids. A phylogeny was constructed for ca . 10% of the species of the clade, based on sequences of four concatenated low-copy nuclear loci. Genetic allopolyploidy was documented using the characteristic pattern of double-labeled gene trees. At least 32% of the species sampled are the result of genetic allopolyploidy and result from 28 distinct tetraploidy events plus an additional six hexaploidy events. This number is a minimum, and the actual frequency could be considerably higher. The parental genomes of most Andropogoneae polyploids diverged in the Late Miocene coincident with the expansion of the major C ₄ grasslands that dominate the earth today. The well-documented whole-genome duplication in Zea mays ssp. mays occurred after the divergence of Zea and Sorghum . We find no evidence that polyploidization is followed by an increase in net diversification rate; nonetheless, allopolyploidy itself is a major mode of speciation. Significance Duplication of genomes following hybridization (allopolyploidy) is common among flowering plants, particularly in the grasses that cover vast areas of the world and provide food and fuel. Here, we find that genome duplication has occurred at a remarkable rate, accounting for at least a third of all speciation events in a group of about 1,200 species. Much of this genome duplication occurred during the expansion of the C ₄ grasslands in the Late Miocene. We find no evidence that allopolyploidy leads directly to a change in the net rate of diversification or correlates with the origin of novel morphological characters. However, as a mode of speciation, the frequency of allopolyploidization is surprisingly high.